Documentation of the traditional Alas food in Southeast Aceh district, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sutrisno IH, Suwardi AB, Navia ZI, Baihaqi, Fadhilah MA. 2021. Documentation of the traditional Alas food in Southeast Aceh District, Indonesia. Biodiversitas 22: 3243-3249. The indigenous and traditional foods of the Alas tribe have a long history and unique traditions that have been passed down for thousands of years. Unfortunately, food tradition is strongly intertwined with the health-related and therapeutic reasoning of food ingredients and preparation methods. However, changes in people's consumption patterns, which prefer fast food, lead to a decline in local knowledge of traditional foods, particularly among the younger generation. Therefore, the aim of this study was to document the traditional Alas food in Southeast Aceh District, Indonesia. The study was conducted in eight subdistricts of Southeast Aceh, Indonesia, namely Lawe Alas, Babul Rahmah, Tanoh Alas, Babussalam, Darul Hasanah, Lawe Bulan, Lawe Sumur, and Bambel subdistricts. The study enlisted 80 respondents (10 from each district) who were chosen at random. The interview was conducted using a questionnaire that covered the respondents' backgrounds, traditional food names, food composition, mode of preparation, and uses. A total of 16 traditional Alas foods were documented, including six types of traditional cuisine and 10 types of traditional snacks. All respondents recognized Manuk Labakh, Ikan Pacik Kule, Puket Megaukh, and Buah Khum Khum as traditional Alas foods. On the other hand, less than 25% of respondents were familiar with some other traditional Alas foods, such as Menekem. The Alas tribe has a great system in place for passing down traditional knowledge from generation to generation. A total of 24 plant species consisting of 21 genera and 14 families was used as traditional Alas food. The Alas tribe prepares a variety of foods from various plant species to maintain their health and contribute to conservation efforts.
Keywords: Traditional knowledge; ceremonies; traditional culinary; Alas tribe; Southeast Aceh